Mapping and Governance Analysis of Gambier Value Chain Upgrading in West Sumatra - Lailatul Rahma; Nia Rosiana; Wahyu Budi Priatna (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Gambier faces various challenges along the value chain, including financing problems and the quality of gambier that does not meet standards because it still uses mixed materials. This study aims to identify value chain mapping, analyze value chain governance patterns, and analyze strategies for improving the gambier value chain in West Sumatra. The research location was purposively selected on the grounds that Lima Puluh Kota Regency and Pesisir Selatan Regency are the largest gambier centers in West Sumatra. This study used the data analysis method from Gereffi and Fernandez-Stark 2016 and ACIAR 2012. The results explained that the activities carried out were planting, harvesting, processing, drying, packing, quality control, sales, with the actors involved being farmers, intermediary traders, cooperatives, large traders, and exporters. The type of governance formed in this gambier value chain is market governance. With low complexity, high codification and high capability variables. The upgrading strategy carried out in this study uses 3 types of upgrading, namely product upgrading, process upgrading, and function upgrading. Product upgrading can be done by making gambier product innovations. Process upgrading can be done by using modern technology in processing to increase theyield and quality of gambier. Function upgrading can be done by building processing facilities that are able to produce high-quality gambier products according to international standards.